Development of gas sensor and camera vision in unmanned ground vehicle for automotive application - Mohamad Syazwan, Mohd Roni (2021)
Rover is a robotic device that integrates a basic system that jointly implements electrical and mechanical components. In this research, a rover using mechanical components consists of a robotic arm, a joint and mechanical grip, a spine chassis, and locomotion, while electrical components include a servo motor, a servo controller, a transmitter and a receiver for vision system and wireless controller its control system is proposed. Besides, as a mobile sensor platform, it should also be fitted with a gas sensor that can show users the number of hazardous threshold gases. This project is intended for control and safety purposes. Furthermore, the main objective of this project is to make a simple robotic rover that is both easy and cost-effective to develop and produce. It is fitted with a robotic arm and real-time vision camera integration to add more versatility to this rover. This rover is fitted with an FPV camera (First Person View), an integrated camera on the rover will provide the pilot of the rover with good vision and direction. This thesis would illustrate the need for adequate, reliable technologies and a well-adapted robotic rover alternative for the local situation, which can significantly improve the safety of workers. Therefore, in various missions, including victim detection, disaster recognition, search and rescue, surveillance and reconnaissance, and risk assessment, the proposed rover technologies can also be used. As for the result, the gas detector and robot vision system were successfully constructed using the MQ-2 gas sensor and the typical FPV system currently available on the market. The MQ gas sensor uses a small heater with an electrochemical sensor inside. They are sensitive to gas. Whenever the gas concentration increases, the resistance will decrease (but the current will increase). It causes a voltage change and is read on the analog output pin. The captured image is sent to the ground station, which includes a monitor connected to the receiver module. The transmitted image frequency is set to 5.8GHz, and many channels can be selected. The image processing unit can give a digital image of the object captured by the camera. The FPV system can be further upgraded, with a larger radius, higher resolution, and object recognition and recognition capabilities. At the same time, advances in computer vision and machine learning are also moving towards more complex systems that can be deployed.